O Cavaleiro nas Cantigas de Santa Maria (Nuntius Antiquus, 2014)
This paper aims to expose the theme of chivalry in the Cantigas de Santa Maria, compiled at the court of King Alfonso X the Wise (1221-1284). The purpose of this study is to approach the following topics: the spiritual and amorous vassalage service of the knight towards the lady and values of chastity, fidelity and faith, present in the selected corpus (eight songs), which deals with the aforementioned issues, examining not only the symbolism of the chivalry, but also the devotion to the Virgin, and how she helps the knight’s religiosity and obedience, who honors the ritual accolade’s oath and the weapons’ watch, rites which are celebrated in the Church.